A model study on the impact of metal ions on pre-vulcanization of concentrated natural rubber latex and dipped-products. Issue 1 (February 2022) - Rojruthai, Porntip; Payungwong, Narueporn; Sakdapipanich, Jitladda T
A model study on the influence of some heavy metal ions on the stability and vulcanization efficiency of uncompounded and compounded high-ammonia natural rubber (HANR) latex was carried out by an exogenous addition and then determined by Brookfield viscometer, mechanical stability time (MST) tester, and tensile testing machine. The case of pre-vulcanized HANR latex with different aging times was determined by the change in the volatile fatty acid (VFA) number, MST, and viscosity. The compounded HANR latex was coagulated by adding Mn 2+ and Mg 2+ while it was unaltered by adding Zn 2+, Fe 2+, and Cu 2+ ions, leading to their colloidal stability. Therefore, these metal ions were chosen further to study the pre-vulcanization of compounded HANR latex. The presence of Zn 2+, Fe 2+, and Cu 2+ in the latex is responsible for the delay in the vulcanization process and changes the appearance of compounded latex. Before compounding, the addition of such metal ions led to the reduction in tensile strength of the obtained gloves. At the same time, there was no effect on the tensile properties of the gloves made from the compounded HANR latex containing the metal ions.